Online Learning Merdeka Belajar Kurikulum Merdeka Program Student Exchange from Universitas Negeri Riau with Universitas Negeri Padang - Armizul C, Muhammad; Isjoni, Isjoni; Ahmal, Ahmal (CV. Rayyan Dwi Bharata, 2024)
Online learning is learning without direct face-to-face interaction between lecturers and students which is carried out online using internet network access. The UNRI-UNP student exchange MBKM program in the FKIP History Education study program at Riau University is a collaboration between FKIP Riau University History Education and FIS UNP History Education which is carried out online. This research aims to describe the implementation of online learning for the UNRI-UNP student exchange MBKM program in the History Education study program, FKIP, University of Riau, academic year 2022/2023. This research method is research with a qualitative approach. Data collection techniques in this research used observation, interviews and documentation. The results of this research describe the implementation of online learning for the UNRI-UNP student exchange MBKM program in the History Education study program, FKIP, Riau University. However, online learning has obstacles in its implementation, students have difficulty understanding the learning material and this is a challenge in itself in online learning.